The effect of leflunomide on cycling and activation of T-cells in HIV-1-infected participants. - Sarah W Read; Mary DeGrezia; Emily J Ciccone; Rebecca DerSimonian; Jeanette Higgins; Joseph W Adelsberger; Judith M Starling; Catherine Rehm; Irini Sereti (PLoS ONE)
Background The pathogenesis of immunodeficiency due to human immunodeficiency virus (HIV)-1 is incompletely understood, but immune activation is believed to play a central role. Immunomodulatory agents that decrease immune activation may be useful in the treatment of HIV-1 infection. Methodology A randomized, double blind, placebo-controlled pilot study of leflunomide for 28 days was performed in participants with HIV-1 infection who were not receiving antiretroviral therapy. Participants randomized to leflunomide were subsequently treated with cholestyramine until leflunomide levels were below detection limit. Findings Treatment with leflunomide was well tolerated with mostly low-grade adverse events. Leflunomide administration reduced cycling of CD4 T cells (by ex vivo bromodeoxyuridine uptake and Ki67 expression) and decreased expression of activation markers (HLA-DR/CD38 co-expression) on CD8 T cells in peripheral blood. In addition, decreased expression of HIV-1 co-receptors was observed in both CD4 and CD8 T cells in the leflunomide group. There were no significant changes in naïve and memory T cell subsets, apoptosis of T cells or markers of microbial translocation. Conclusions Leflunomide was effective in reducing immune activation in the setting of chronic HIV-1 infection suggesting that targeting immune activation with immunomodulatory agents may be a feasible strategy. Trial registration ClinicalTrials.gov NCT00101374.